(untitled) (Archives of Mechanics - Test, 2000)
The integrity assessment of defective pipelines represents a practically important task of structural analysis and design in various technological areas, such as oil and gas industry, power plant engineering and chemical factories. It is very essential to evaluate the load-carrying capacities of defective pipelines in order to judge safely their working life. In this paper, an iterative algorithm is presented for the kinematic limit analysis of 3-D rigid-perfectly plastic bodies. A numerical path scheme for radial loading is adopted to deal with complex multi-loading systems. The numerical procedure has been applied to carry out the plastic collapse analysis of pipelines with part-through slots under internal pressure, bending moment and axial force. The effects of various shapes and sizes of part-through slots on the collapse loads of pipelines are systematically investigated and evaluated. Some typical failure modes corresponding to different configurations of slots and loading forms are studied.